العلاقة السببية بين سعر الصرف واحتياطي الصرف الأجنبي في الجزائر باستخدام نموذج تصحيح الخطأ Vecm للفترة 1990-2020 - بن عيسى, كمال الدين; حزام, نسيم; بونشادة, نوال (جامعة الوادي - University of Eloued, 2023)
This study aims to analyze the causal relationship between the exchange rate and foreign exchange reserves in Algeria in the long and short terms during the period 1990-2020, using the VECM error correction model for the period 1990-2020. The study concluded that there is a statistically negative and moral effect - in the short term - of the foreign exchange reserve on the exchange rate in Algeria, where the higher the exchange reserve by 1%, the higher the exchange rate of the dinar against the dollar by 0.11%. The foreign exchange rate in Algeria, where whenever the exchange reserve rises by 1%, the exchange rate of the dinar against the dollar decreases by 0.16%.
Causal relationship between the exchange rate and foreign exchange reserves in .Algeria using the VECM model for the period 1990-2020
مقال
Keywords: سعر الصرف ; احتياطي سعر الصرف الأجنبي ; نموذج تصحيح الخطأ; Exchange rate, foreign exchange rate reserve, Error correction model